Estudo de viabilidade técnico-econômica de sistemas fotovoltaicos interligados à rede elétrica em diferentes cenários de geração - Ikuta Júnior, Emerson Shinji (2014)
On this paper it is presented the study of technical and economic feasibility of photovoltaic systems grid connected on homes, shops and photovoltaic power plants. This paper presents the theoretical study through the basic concepts about photovoltaic energy, the assumptions that justifies this paper, how installations and measures work on photovoltaic systems grid connected, considering the standards and rules that goes on. By the energy bills of different locations, one house and two shops were developed the study cases. Using the energy consumption of these locations to size the photovoltaic systems and develop the settings of energy consumption and generation. Comparing the energy bills before and after the estimations after the installment of the photovoltaic systems and considering the net metering, analyzing the payback time on each setting. On photovoltaic power plants it is used the collected data of biddings of photovoltaic power plants, finance analysis and the cost of energy on energy market it is reviewed the payback time. By the end, studying the feasibility of the different settings approached.